(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
A simple, reliable, rapid, precise, sensitive and validated RP-HPLC method has been developed to determine Aspirin and Prasugrel in synthetic mixture form. Chromatographic separation achieved isocratically on Luna C18 column (5µm, 150mm × 4.60mm) and acetonitrile: 0.05M ammonium acetate buffer (pH 4.5) in the ratio of 75:25 (v/v) as the mobile phase, at a flow rate of 0.6 ml/min. Detection was carried out at 245 nm. Parameters such as linearity, precision, accuracy, recovery, specificity and ruggedness are studied as reported in the ICH guidelines. The retention times for Aspirin and Prasugrel was found to be 2.25±0.5 and 8.72±0.5 min respectively. Linearity for Aspirin and Prasugrel was in the range of 75-375μg/ml and 10-50μg/ml respectively. The mean recoveries obtained for Aspirin and Prasugrel were 99.58 and 99.48 % respectively and RSD was less than 2. The correlation coefficients for all components are close to 1. Developed method was found to be accurate, precise, selective and rapid for simultaneous estimation of Aspirin and Prasugrel.